Homeroom Teacher's Action On Hyperactive Students Of MIN 3 West Aceh - Kurniawan, Ade; Ismawati, Diyah (Program Studi Pendidikan Agama Islam (PAI), 2022)
This study aims to determine the behavioral tendencies of hyperactive students in State Islamic Elementary School 3 of West Aceh and how the homeroom teacher manages hyperactive students in MIN 3 West Aceh. This study employs a descriptive qualitative methodology. Observations, interviews, and documentation were employed as data gathering strategies. This investigation was carried out at State Islamic Elementary School 3 of West Aceh. This study involved one principal of State Islamic Elementary School 3 of West Aceh and two homeroom teachers who teach hyperactive students. Based on the study's findings, it is apparent that the hyperactive students of MIN 3 Aceh Barat exhibit motor and mixed hyperactivity with a combination type. The homeroom activities for dealing with hyperactive students consist of (1) arranging seats, (2) issuing warnings, (3) providing hyperactive students with guidance, and (4) building a madrasa setting appropriate to the growth of hyperactive students.